30th anniversary of the renewal of diplomatic relations between the State of Israel and the Republic of Serbia - Vilan, Jahel (Napredak, 2022)
Historical closeness of the Serbian and Jewish nations, also expressed through their suffering and torments during World War Two is nowadays best reflected in sincere and friendly relations between the two nations and the two countries. The fact that after the Six Day War in 1967, according to the decision of the Yugoslav government at the time, the diplomatic relations were briefly interrupted officially, did not affect mutual understanding and cooperation whenever it was possible. Since spring 1992 the diplomatic relations were raised to the highest level, proving that, although Serbia is not Israel0s geographical neighbour, it is the neighbour in the heart of this nation. Through testimonies and examples of the persons whose deeds wove the threads of honest friendship and understanding, this text will speak of good bilateral relations of the two countries and the need to help each other while facing joint challenges in the present, while protecting our national interests and identities. We see the future in a more active and profound engagement in all aspects of our lives – economy, tourism, investments, culture, sport and, of course, science.